Convection‐permitting modeling with regional climate models: Latest developments and next steps. (16th August 2021) - Lucas‐Picher, Philippe; Argüeso, Daniel; Brisson, Erwan; Tramblay, Yves; Berg, Peter; Lemonsu, Aude; Kotlarski, Sven; Caillaud, Cécile
Abstract: Approximately 10 years ago, convection‐permitting regional climate models (CPRCMs) emerged as a promising computationally affordable tool to produce fine resolution (1–4 km) decadal‐long climate simulations with explicitly resolved deep convection. This explicit representation is expected to reduce climate projection uncertainty related to deep convection parameterizations found in most climate models. A recent surge in CPRCM decadal simulations over larger domains, sometimes covering continents, has led to important insights into CPRCM advantages and limitations. Furthermore, new observational gridded datasets with fine spatial and temporal (~1 km; ~1 h) resolutions have leveraged additional knowledge through evaluations of the added value of CPRCMs. With an improved coordination in the frame of ongoing international initiatives, the production of ensembles of CPRCM simulations is expected to provide more robust climate projections and a better identification of their associated uncertainties. This review paper presents an overview of the methodology to produce CPRCM simulations and the latest research on the related added value in current and future climates. Impact studies that are already taking advantage of these new CPRCM simulations are highlighted. This review paper ends by proposing next steps that could be accomplished to continue exploiting the full potential of CPRCMs. This article is categorized under: Climate Models and Modeling > Earth System Models Abstract : Snapshots of summertime convection over continental Europe as simulated by a 12‐km "conventional" convection‐parameterized regional climate model (left) and a 2‐km convection‐permitting regional climate model with deep convection treated explicitly (right) on July 13, 2006, 12:00 UTC. The colored shading denotes the 15 min precipitation (mm/h), and the gray shading a cloud visualization. Note the small, but intense convective cells (above 10 mm/h) in the convection‐permitting regional climate model (right) compared to the widespread drizzle and light rain (mostly below 2 mm/h) in the regional climate model (left).